Multi-Criteria Optimization of Laser Cladding: Integrating Process Parameters and Costs - Óscar Barro; Felipe Arias-González; Ana Mejías; Fernando Lusquiños; Daniel Wallerstein; Jesús del Val; Juan Pardo; Juan Pou (Journal of Manufacturing and Materials Processing, 2025)
This study presents a novel approach in the laser cladding optimization field by integrating economic analysis with performance optimization. Despite extensive research on laser cladding technical performance, its economic evaluation—particularly when merged with productivity assessment—has scarcely received attention. This work addresses this gap by integrating an economic and productivity analysis with a standard performance evaluation through the employment of a multi-criteria optimization approach to balance technical and economic performances. To achieve this objective, a multi-parametric optimization via response surface methodology (RSM) and desirability function analysis has been developed. Results indicate that the employment of desirability analysis after RSM modeling is a valuable approach for laser cladding analysis, allowing the particular weighting of each result and providing the possibility of selecting processing parameters depending on the specific objective at any given time.